Sosialisasi Social Distancing Bagi Generasi Milenial Di Desa Padak Guar Kecamatan Sambalia Kabupaten Lombok Timur - Lalu Hendra Maniza; Sulhan Hadi; Abdul Hafiz (Abdi Masyarakat, 2020)
This community service report is entitled "Social Distancing Socialization for Millennial Generation in Padak Guar Village, Sambalia District, East Lombok Regency". The goal of this commonity service is, first, to raise awareness about the importance of social distancing and physical distancing; secondly, to provide knowledge for people in Padak Guar Village, East Lombok Regency about Covid 19, ways of transmission, symptoms and treatment and thirdly, to provide knowledge about how to carry out daily life activities so that people can meet their daily needs so that their economies remain walk normally. The method applied is face to face and discussion. The results obtained from this Community Service are increasing knowledge for the participants, in this case the people in Padak Guar Village, about the awareness of the importance of social distancing and physical discourse to agains the spread of the corona virus.